Assessing the crossdisciplinarity of technology‐enhanced learning with science overlay maps and diversity measures. (1st August 2013) - Kalz, Marco; Specht, Marcus
Abstract This paper deals with the assessment of the crossdisciplinarity of technology‐enhanced learning (TEL). Based on a general discussion of the concept interdisciplinarity and a summary of the discussion in the field, two empirical methods from scientometrics are introduced and applied. Science overlay maps and the Rao‐Stirling diversity index are used to analyze the TEL field with a scientometric analysis. The science overlay maps show that a wide variety of disciplines contributes to research in the field. The analysis reveals that the field has been operating on a relatively high level of crossdisciplinarity in the last 10 years compared with six other fields of reference. Only in 2004 a decrease in the level of crossdisciplinarity could be identified.